2007
DOI: 10.1007/s00418-007-0307-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of orchidectomy on thyroid C cells and bone histomorphometry in middle-aged rats

Abstract: This study was to evaluate the effect of androgen deficiency on thyroid immunoreactive C-cells and bone structure and function in a male orchidectomized middle-aged rat model. Fifteen-month-old male Wistar rats were divided into orchidectomized (Orx) and the sham-operated control (Sham) group. In the Orx group significant decreases (P < 0.05) were found in the volume of C cells (by 14%), their relative volume density (by 13%) and serum calcitonin concentration (by 54%) compared to the controls. Analyses of tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(74 citation statements)
references
References 46 publications
4
70
0
Order By: Relevance
“…The biochemical findings showed a significant increase in Pi urinary excretion, together with a decrease in serum Ca 2+ and Pi concentrations after Orx, which is consistent with our previous results (17)(18)(19). The observed increase in urine Pi concentration after Orx could be a consequence of the reduced expression of NaPi 2a cotransporter in the epithelial cells of kidney proximal tubules (19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The biochemical findings showed a significant increase in Pi urinary excretion, together with a decrease in serum Ca 2+ and Pi concentrations after Orx, which is consistent with our previous results (17)(18)(19). The observed increase in urine Pi concentration after Orx could be a consequence of the reduced expression of NaPi 2a cotransporter in the epithelial cells of kidney proximal tubules (19).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies have shown that the orchidectomy-induced lack of steroid hormones caused an enhancement in urinary Ca 2+ excretion and decreased serum Ca 2+ and Pi concentrations (17,18), along with an increment in Pi urinary wasting, in middle-aged male rats (19). These chan ges have led to a decrease in the bone tissue compactness (17,18), which increases the risk of bone fragility (9).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously reported that aged orchidectomized (Orx) male rats represent an adequate animal model for simulation of male osteoporosis due to androgen deficiency and subsequent skeletal effects [8]. Namely, many investigations have shown that androgen deficiency after Orx leads to reduction of bone mass in male rats and mice [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, C cells may also be very important in the pathogenesis of osteoporosis. We have previously reported that androgen deficiency after Orx modulated the structure of thyroid C cells and inhibited the synthesis and release of CT in middle-aged rats [11].…”
Section: Introductionmentioning
confidence: 99%
“…One of the symptoms of Low testosterone levels result in decreased bone mass. Filipovic et al (2007) have evaluated the eVect of androgen deWciency on thyroid immunoreactive C-cells, and on bone structure and function in the male orchidectomized middle-aged rat model Orx. In the Orx group signiWcant decreases (P < 0.05) were found in the volume of C cells (by 14%), their relative volume density (by 13%) and serum calcitonin concentration (by 54%) compared to the controls.…”
Section: Hormone Cell Biologymentioning
confidence: 99%